The Attention Apparatus: Conditions and Affordances of News Reporting in Hybrid Media Events of Terrorist Violence. (9th August 2022) - Uusitalo, Niina; Valaskivi, Katja
ABSTRACT: Acts of terrorist violence become repeatedly the focus of amplified attention in Western media. These acts spur hybrid media events where both news media and media users create and share information and interpretations of the event. Large news organizations play an integral role in attracting, steering and regulating attention in hybrid media events of terrorist violence. This article develops a theoretical conceptualization of the news organization as an attention apparatus. We argue that the apparatus consists of two dimensions: First, three conditions constrain the workings of the attention apparatus: perceived audience expectations, professional conditions of journalism and societal responsibilities of journalism. Secondly, there are three temporal affordances through which attention is managed: immediacy, liveness and interruption. We come to these conclusions through empirical research on newsroom practices in terrorism news production at the Finnish Broadcasting Company (Yle). Our data consist of thematic interviews (N = 33) with Yle journalists, producers and content managers as well as newsroom observations (14 days) conducted at Yle News and Current Affairs departments. The data is interpreted through a grounded theory approach. The article highlights how the temporal affordances enable reporting in hybrid media events but also clash with established conditions of news reporting.